Legal Review of Defense Human Resource Management in the VUCA Era: Based on Law Number 3 of 2002 - Agus Adriyanto (Faculty of Law, Universitas Pekalongan, 2023)
Defense human resources in the VUCA era (Volatility, Uncertainty, Complexity, and Ambiguity) based on Law Number 3 of 2002 concerning state defense. The VUCA era, which is characterized by rapid change, uncertainty, complexity, and ambiguity, demands changes in the strategy of managing human resources in the defense sector. This study uses a normative legal method, with a statutory approach and analysis of literature related to defense human resource policies. The results of the study indicate that Human Resource Management in the defense sector, in accordance with Law Number 3 of 2002, must adapt to the challenges of the VUCA era (Volatility, Uncertainty, Complexity, Ambiguity). The need for superior and adaptive human resources is increasingly crucial, requiring them not only to have technical skills, but also a deep understanding of information and communication technology, and the ability to deal with cyber threats. In addition, mastery and maintenance of advanced main weapons systems (alutsista) are indicators of the reliability of human resources. However, existing regulations are still not fully in line with VUCA dynamics, so the government needs to formulate relevant training policies, including adjusting the curriculum at military academies. In addition, it is important to regulate the legality of international training programs and provide legal protection for personnel, including guarantees of basic rights such as compensation and medical care. Comprehensive policies and regulations will strengthen risk management and enable decentralization of decision-making, so that personnel can be more flexible and effective in facing evolving challenges.